Benchmarking de las unidades de emprendimiento en las universidades de Colombia (2016)
Universities have raised awareness about the importance of creating an Entrepreneurship Unit within the educational institutions. This is a powerful tool to encourage entrepreneurship among students and so it is a channel of communication between academia and industry, which allows build a support network for projects generated within an educational institution. In the article the key factors of entrepreneurship, which must be taken into account when structuring a unit of entrepreneurship. Then are presented some success cases at universities in Colombia similar to the American University Foundation. Finally, is highlighted the importance of promoting innovation and entrepreneurship inside the academic institutions.